Why It Matters What We Do: Arab Citizens' Perceptions of the European Union after the 2011 Uprisings - Kressen Thyen (German Institute of Global and Area Studies (GIGA), 2018)
In the Middle East and North Africa, EU foreign policy has tended to prioritise regime stability over democratisation. Existing research has argued that this could create anti-European sentiment in the respective populations. However, empirical evidence on the relationship between the EU's stance towards regime change and citizen attitudes remains rare. Focusing on Morocco and Egypt, this study uses a mixed-methods approach, combining qualitative case studies with original survey data to examine whether the EU's divergent responses to the 2011 uprisings in these two countries are mirrored in regime opponents' support for EU cooperation.
Keywords: 300; EU Mediterranean policy; Arab uprisings; external democratisation; foreign policy perceptions; survey research